Allied health professional rural education: Stellenbosch University learners’ experiences - M Pillay; J Bester; R Blaauw; A Harper; A Msindwana; J Muller; L Philips (South African Medical Association, 2016)
Background. Rural clinical training is not widely established or documented for allied health sciences (AHS) learners. This article focuses on the experiences of AHS learners from Stellenbosch University’s uKwanda Rural Clinical School.Objective. To explore learners’ practices with regard to rural clinical training in the AHS.Methods. A total of 22 documented reflections and seven educator or learner semi-structured focus group discussions, using critical conversations, were analysed with methods such as textual and thematic analysis and qualitative research software (ATLAS.ti, Germany).Results. The perception of rural clinical training was reported as an overwhelmingly positive experience. Practices positioned ‘rural’ as a catalyst for developing learners’ emerging identities as policy brokers, and as best when delivered by team participation. Professional education curricula were reported as dependant on: (i) context; (ii) educators; and (iii) how time was managed.Conclusion. Rural-based learning is a humanising experience for health science learners.